A Syntactic Analysis Of Arabic-english Intra-sentential Code-switching In Jordanian University Students’ Speech - Alamaren, Eman Mohammad Hussein (2022)
Languages are not perfectly complete by themselves. Language contact is the process of contacting languages to allow speakers' connection. This contact results in some changes in languages including code-mixing phenomenon. The present study aims at investigating the syntactic patterns of Jordanian Arabic-English code-mixing in Jordanian students' speech in Yarmouk University. Firstly, the study determines the types of patterns and the syntactic aspects of code-mixing in Jordanian Arabic-English pair in Yarmouk University students' speech. Secondly, it determines the effect of the syntactic differences between Arabic and English on Arabic structure when code-mixing is performed. Thirdly, it explores the most frequently used English syntactic categories that students tend to use when performing codemixing. Finally, the study examines the occurrence of Poplack's constraints in Jordanian Arabic-English code-mixing. To this end, a research design involving both qualitative and quantitative approaches was adopted. That is, tape-recorded conversations between students in Yarmouk University were qualitatively analyzed to identify the types of patterns of code-mixing, and then the conversations were quantitatively analyzed to explore the numbers of the used English constituents. The collected data were analyzed using thematic analysis and frequency distribution techniques. The findings revealed that there are three types of code-mixing; each type includes a number of patterns, and these types of patterns are gradual in terms of familiarity and frequency of occurrence. Verb-Object pattern occupies the first position followed by Determiner-Noun pattern, while Preposition-Noun pattern occupies the last position.